Parenting infants at the times of COVID-19: a cross-sectional study on parental stress in the province of Modena (Northern Italy) - Righi, Elena; Ferrari, Eleonora; Lucaccioni, Laura; Fasano, Marco; Righi, Beatrice; Trevisani, Viola; Palandri, Lucia (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: The advent of the COVID-19 pandemic and the consequent measures to prevent virus’s spread particularly affected families with young children, that represent a complex system characterized by a constant interaction between the infant’s and the parent’s well-being. The present study aims to investigate the parenting stress experienced by parents with 6-month-old healthy infants surveyed from September 2019 to April 2021 in the Modena province (Northern Italy). Research design and methods: We carried out a cross-sectional study using the Parenting Stress Index-Short Form (PSI-SF) questionnaire to assess stress levels in the parent-child system. Since the questionnaire is meant to be self-completed by the participant, the survey could continue to be conducted remotely during the pandemic lockdown months. Results: Most parents exhibited physiological stress scores, but parents who have been interviewed during the pandemic period had a higher prevalence of stress problems. Subjects in the COVID group also showed a drop in the defensive response and a lower prevalence of stress problems when parenting siblings. Conclusions: These findings underline the importance of early detection of isolation’s negative effects on households and strengthen the need for tailored familial support during stressful events, in order to promote parent and children's emotional well-being.